2015
DOI: 10.1037/lhb0000131
|View full text |Cite
|
Sign up to set email alerts
|

Interviewing strategically to elicit admissions from guilty suspects.

Abstract: In this article we introduce a novel interviewing tactic to elicit admissions from guilty suspects. By influencing the suspects' perception of the amount of evidence the interviewer holds against them, we aimed to shift the suspects' counterinterrogation strategies from less to more forthcoming. The proposed tactic (SUE-Confrontation) is a development of the Strategic Use of Evidence (SUE) framework and aims to affect the suspects' perception by confronting them with statement-evidence inconsistencies. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 29 publications
(56 reference statements)
5
70
1
Order By: Relevance
“…As in previous studies using the SUE framework to elicit new information (Tekin et al, 2015, 2016), all mock suspects in this study were guilty. The rationale behind this was that previous studies using a similar design have shown innocent suspects to be forthcoming to a very high extent (Luke et al, 2014; Tekin et al, 2014), and we had no reason to assume that innocent suspects would be less forthcoming in the present study.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…As in previous studies using the SUE framework to elicit new information (Tekin et al, 2015, 2016), all mock suspects in this study were guilty. The rationale behind this was that previous studies using a similar design have shown innocent suspects to be forthcoming to a very high extent (Luke et al, 2014; Tekin et al, 2014), and we had no reason to assume that innocent suspects would be less forthcoming in the present study.…”
Section: Introductionmentioning
confidence: 73%
“…In suspect interviews, the use of evidence is often at the core. Unfortunately, to date only few studies have provided knowledge on the link between evidence disclosure and information elicitation (e.g., Tekin et al, 2015; Walsh and Bull, 2015). Therefore, this study was designed to examine how different evidence disclosure modes affect the elicitation of new critical information.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, an experimental study has also found that strategic evidence disclosure led mock suspects to reveal more information compared to when the interviewer disclosed STRATEGIC DISCLOSURE OF EVIDENCE 13 the evidence early or not at all (Tekin et al, 2015). By strategically disclosing evidence, the interviewer manipulated the suspects' perceptions of how much evidence the interviewer held.…”
Section: Research and Arguments From Psychologymentioning
confidence: 99%